Systematic Literature Review of Art Reception Survey (ARS) on Aesthetic Perception Studies And Future Research Directions - Wan Juliana, Emeih Wahed; Saiful Bahari, Mohd Yusoff; Noorhayati, Saad; Patricia Pawa, Pitil (Human Resource Management Academic Research Society, 2021)
Aesthetic studies are engaged with various visual stimuli connected to human senses, which project different perceptions based on one’s aesthetic experiences. The right output of the process is a ‘symptom’ of ‘delighted’ art which creates positive experiences in measuring a ‘good taste’ of art. This paper’s aim was to review the ARS instrument on different domains of aesthetic studies namely textile, art writing, painting, figurative, abstract painting, representational art and film. The analyses comprised seven adaptations of the Art Reception Survey, indicating the properly designed instrument suited for the screening purposes. The findings demonstrated the influential factors of aesthetics including prior knowledge, art knowledge, familiarity and art connection. The findings also suggested the basis of the instrument adaptation in aesthetic studies, combined with the construction of the understanding between the trained and untrained perceivers.